Lohnungleichheit, Erwerbsbeteiligung und Beschäftigung - Joachim Möller; Marion König (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2011)
– This contribution focuses on the relation between wage inequality, participation behavior and employment and the analysis in the project 'Flexibility of the wage distribution, inequality and employment'. In this project we investigate whether the popular idea of an encrusted German labor market with institutional regulations, minimum wages, high reservation wages, union power or insider behavior is consistent with the actual conditions. At first we critically assess the hypothesis that wage compression in Germany leads to employment losses. It can be shown theoretically that higher wage dispersion lower labor market participation as a negative side-effect. Empirical analyses support this result. A higher regional wage level as well as low unemployment – as an indicator for the stability of jobs – come along with high participation. A rise in wage dispersion in the lower part of the wage distribution is connected with decreasing employment participation, in the upper part with rising employment participation. As a further result it is shown that interdependencies between regions strongly matter. Additionally we highlight stylized facts about the development of wage inequality. We compare the US and Germany – countries with high and low wage flexibility respectively – based on harmonized micro data. We analyze the hypothesis that rigidities due to institutional influences imply a deformation of the wage distribution in the left tail. Such a characteristic wage compression would have to appear particularly for groups of low wage workers in countries like Germany. The comparison with the US labor market suggests the assumption that the deformation of the German wage structure with negative impacts on employment is a distorted picture. A further topic addresses the consequences of setting bounds to the extending inequality in the lower part of the wage distribution by introducing a wage floor. We focus on the effects of a minimum wage on wage inequality and employment. This minimum wage was introduced in 1997 in the German construction sector related to the German Workers Posting Law. We find positive wage effects of the minimum wage regulation in Eastern as well as in Western Germany, albeit the wage reaction in Eastern Germany was considerably larger. When it comes to employment effects, negative effects arise for Eastern Germany and positive for West Germany, although the latter are not always statistically significant. This result shows that a binding minimum wage does not necessarily imply negative employment effects. Finally, this contribution deals with a specific aspect of the wage inequality, the gender pay gap. The focus here is on the influence of the regional context. Having controlled for differences in individual characteristics, education and work places between men and women we show that the gender-specific wage differential is considerably higher in rural than in metropolitan areas. This differential has decreased notably in the last three decades in both regional types. The pay gap between young women and men in rural areas, in an environment with low firm density, is almost constantly ten percentage points higher during the whole observational period than in metropolitan settings. This result is consistent with a theoretical model that additionally takes into account market power of firms.
Keywords: 330; Lohnunterschied - internationaler Vergleich; Lohnstruktur; Erwerbsbeteiligung; institutionelle Faktoren; Beschäftigungseffekte; Lohnpolitik; Mindestlohn; Lohnflexibilität; Lohnstarrheit; geschlechtsspezifische Faktoren; erwerbstätige Frauen; erwerbstätige Männer; regionale Faktoren; regionaler Arbeitsmarkt; Geringverdiener; USA; Bundesrepublik Deutschland